Censorship of electronic information in academic libraries - Catral, Aldwin B.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
Computers have become the most versatile piece of equipment in history today. They make our tasks easier, allowing us to work more efficiently. They have integrated themselves to almost everything we do, from driving cars to making business transactions, from researching to leisure, and from music to literature to art. However, there has been growing concern with the effect of computers in today's society. Piracy and misinformation are just an example of these. The most prevalent issue is censorship.
With the advent of the Internet, it has all been but impossible to monitor and censor information. Couple that with the growing number of ways information can be stored and accessed with a computer, the task seems daunting. Not to mention the innate fear librarians have of censoring materials.
Academic libraries are the forefront of computerization. Though there are information centers available nowadays, the true measure of society's information needs can be found in the education system. Thus, the academic library is the premier source of information regarding computerization.
This thesis is the first to study the censorship policies and procedures of academic libraries. It compares these findings in the hope of explaining and suggesting a standard set of rules. The study is descriptive in nature. Seven libraries were approached, however, only three responded.
The three who responded had very similar policies. They had no specific written guidelines regarding what should be censored. However, that is not to say that rules are absent. Rather, the censors are entrusted to interpret the school's or library's mission and vision. That is, the decision is left largely to the staff or board.
Also, there is current trend of transforming a library from a storehouse of knowledge into an access point of information. This is evident with the current inclination of subscribing to other institutions for providing information and materials such as electronic journals and databases.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Censorship